What teacher educators consider as best practices in preparing pre-service teachers for teaching mathematics in multilingual classrooms - Essien, Anthony A. (Faculty of Education, University of the Free State, 2010)
This paper reports on an investigation into what teacher educators consider to be best practices in how to prepare pre-service teachers to effectively deal with the challenges of teaching Mathematics in multilingual contexts, and how what teacher educators consider as best practices inform their own classroom practice. Twelve teacher educators (TEs) from four universities in a province in South Africa participated in the study. Through a qualitative analysis of the interviews, five practices emerged as best practices for these teacher educators: the use of code switching, the creation of an environment of trust in the classroom, the use of one (rather than two) medium of instruction, namely English, the use of linguistic metaphors that the languages present in the class potentially provide for use in mathematics, and, finally, the creation of an awareness of the multilingual context in which pre-service teachers would teach at the end of their qualification. Given that most teachers in South Africa teach in multilingual classrooms and teacher education research on mathematics education has not, thus far, focused on multilingual mathematics education, it is hoped that these five practices would serve as an inducement for both teacher educators and researchers alike. The author also cautions against the adoption of imported practices from other countries and argues that in delineating practices that are more likely to work in the South African context, it is important to bear in mind the distinctive nature of multilingualism in South Africa.
Keywords: Multilingual mathematics education; Teacher educators; Pre-service teachers; Classroom practice